ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI BOKAR (BAHAN OLAH KARET) DI KABUPATEN BATANGHARI - Lumban Gaol, Elisabeth; Mara, Armen; Oktari Ulma, Riri (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
This study aims to (1) the progress bokar production, the land area to produce crops, the land area of ​​old plants, the amount of labor, rainfall and number of days of rain in Batanghari regency during the period 2001 to 2015 (2) Determine how much influence hectarage produce, the land area of ​​old plants, the amount of labor, rainfall and number of days of rain to the production bokar in Batanghari regency during the period 2001-2015. The data used in this research is secondary data time series (time series) for 5 years (2001-2015). Test data is stationary using the unit root test Phillip Perron (PP). The analysis model is a linear regression. The test model using normality test, multicollinearity, heteroscedasticity test and autocorrelation test. The results showed that the area of ​​cultivated land, the area of ​​old plantation, the amount of labor, rainfall and amount of rain days together significantly affect the production of bokar in Batanghari regency. Partially, the factors that have a positive and significant effect on bokar production in Batanghari Regency are the area of ​​cultivated land and the amount of labor. Factor area of ​​old crop land have negative and significant effect, while rainfall factor and rainy day partially have no significant effect on bokar production.